Business English meetings : instant agendas - Comfort, Jeremy, 1953-; Brieger, Nick, 1948- (Penguin Books, 1998)
Učebnice konverzačních témat hospodářské angličtiny s metodickými poznámkami pro učitele
Keywords: angličtina; oborová terminologie; obchodní komunikace; English language; communication in business; terminology (professional); učebnice; textbooks; metodické příručky; methodological manuals